Association between blood lead levels and hyperlipidemiais: Results from the NHANES (1999–2018) - Zhang, Yangchang; Liu, Weiwei; Zhang, Wei; Cheng, Rui; Tan, Andi; Shen, Shisi; Xiong, Yang; Zhao, Limei; Lei, Xun (Frontiers in Public Health, 2022)
Background: Research on the association between blood lead (Pb) and lipid biomarkers have yielded inconsistent results, and epidemiological studies on blood Pb levels and hyperlipidemia are scarce. The present study aimed to examine the association between blood Pb levels and hyperlipidemia in adults from the National Health and Nutrition Examination Survey (NHANES). Methods: A total of 33,728 participants in the NHANES from 1999 to 2018 were included in the final analysis. Hyperlipidemia was determined based on the National Cholesterol Education Program guidelines. Blood Pb levels were assessed using inductively-coupled plasma mass spectrometry. Weighted multivariable logistic regression analysis and subgroup analysis were conducted to determine the correlation between blood Pb levels and hyperlipidemia. Results: In the multivariable logistic regression model, high blood Pb levels were significantly associated with hyperlipidemia after adjusting for confounders (OR 1.56; 95%CI: 1.26–1.92). Furthermore, elevated blood Pb levels were associated with an increased risk of hyperlipidemia across the four quartile (Q) groups (Q1: OR 1.00; Q2: OR 1.15 [95%CI: 0.98–1.36]; Q3: OR 1.50 [95%CI: 1.27–1.78]; and Q4: OR 1.30 [95%CI: 1.10–1.52]; P for trend <0.001). Significant moderating effects were found in the subgroup analysis stratified by age, hypertension, and diabetes (P<0.05). In sensitivity analysis, the ORs for hyperlipidemia across the quartiles of blood Pb levels were 1.00, 1.17 (95%CI: 0.99–1.38), 1.55 (95%CI: 1.31–1.85), and 1.36 (95%CI: 1.15–1.60) for Q1, Q2, Q3, and Q4, respectively (P for trend <0.001) after removing adults with arteriosclerotic cardiovascular disease. Conclusion: The current study showed a positive association between blood lead levels and hyperlipidemia.